PENGARUH MODEL ROLE PLAYING TERHADAP KEMAMPUAN PROBLEM SOLVING SOSIAL SISWA KELAS V SEKOLAH DASAR - Fitriana, Aidilla; Nuriyanti, Risma; Koswara Adiredja, Rajji (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Social problem solving skills are essential competencies that elementary school students need to develop in order to deal with various problems encountered in their daily lives. However, these skills have not yet been well developed, making it necessary to implement an appropriate learning model that actively engages students, one of which is the role playing learning model. This study aimed to determine the effect of the role playing learning model on the social problem solving skills of fifth grade elementary school students. This study employed a pre-experimental research method using a One Group Pretest–Posttest Design. The participants consisted of 21 fifth grade students from an elementary school in Garut Regency. Data were collected through an essay test consisting of 20 items based on four indicators of social problem solving skills. The data were analyzed using descriptive statistics, the Shapiro Wilk normality test, and the paired-samples t-test for hypothesis testing. The results showed that the mean pretest score increased from 45.8 to 69.2 on the posttest. The normality test indicated that the data were normally distributed, while the paired samples t-test yielded a significance value of 0.000, which was lower than 0.05, indicating that was rejected and was accepted. Therefore, it can be concluded that the role playing learning model has a positive effect on the social problem solving skills of fifth grade elementary school students.